KOMODITAS KEDELAI DALAM HEGEMONI EKONOMI NEOLIBERALISME (Studi Kasus Tata Produksi dan Tata Niaga Kedelai di Kabupaten Grobogan, Jawa Tengah) - Sitaresmi, Cike (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
Neoliberalism has been secured through the policies of the Bretton Woods institutions , the IMF ,the World Bank and the World Trade Organization (WTO). Hegemony economic and political factors produced the emergence of a neoliberal regime with a predatory capitalist oligarchy playing an ever greater role in Indonesian agriculture,especially soybean comodity. This thesis also describes the relationship of agricultural policy with the soybean self-sufficiency in terms of the flood of imported soybeans. . This research using qualitative methods, writer take the location of research in Grobogan Regency as a representation of the neoliberal economic hegemony in soybean commodity. Grobogan Regency known as the center of soybean production in Central Java but in fact Grobogan Regency is not self-sufficient in soybeans and fall in the soybean imports trapped. Keywords: neoliberalism , hegemony, soybean commodity, self sufficient